2021
DOI: 10.1108/jaar-04-2021-0115
|View full text |Cite
|
Sign up to set email alerts
|

Performance and (non) mandatory disclosure: the moderating role of the Directive 2014/95/EU

Abstract: PurposeThis paper investigates whether and how Directive 2014/95/EU affects financial performance as well as its moderation effect on the relationship between financial and non-financial performance, involving different stakeholders' perspectives.Design/methodology/approachWe adopted the panel data approach to perform random effects regression analysis on a sample of 435 European listed non-financial companies, considering a timeframe of six years. Furthermore, the moderation effect of the Directive 2014/95/EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 42 publications
3
27
1
Order By: Relevance
“…Fonseka et al ., 2019) which found that mandatory environmental disclosure reduces the Cost of Debt . Our findings also expand those of Cupertino et al . (2022a) that found no evidence about the relationship between mandatory non-financial disclosure and the Cost of Debt .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Fonseka et al ., 2019) which found that mandatory environmental disclosure reduces the Cost of Debt . Our findings also expand those of Cupertino et al . (2022a) that found no evidence about the relationship between mandatory non-financial disclosure and the Cost of Debt .…”
Section: Discussionsupporting
confidence: 92%
“…In the light of the evidence presented in the previous section, we found that, in contrast with Cupertino et al (2022a) and Goel (2021), non-financial disclosure regulation had a positive effect on operating profitability and shareholders' returns. An explanation of this result can be that the regulation obliged companies to be transparent about their internal practices, reducing information asymmetries.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The dependent variable – non-financial performance – is proxied by the average ESG performance of the sample firms. The choice of using ESG scores to depict non-financial performance is consistent with the main stream of literature (Bodhanwala and Bodhanwala, 2021; Chairani and Siregar, 2021; Cupertino and Vitale, 2022). The ESG data were retrieved from the Refinitiv Eikon database, which is considered one of the leading global ESG databases (Cheng et al , 2014; Faizul, 2017; Qiu et al , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Performance and (non) mandatory disclosure: the moderating role of the Directive 2014/95/EU Cupertino et al (2022) shed light on how Directive 2014/95/EU affects financial performance as well as its moderation effect on the relationship between financial and non-financial performance. The authors argued that non-financial regulation negatively affects firms' operating profitability and shareholder value while produces no effects on debtholders' returns.…”
Section: Integrated Reporting Quality and Cost Of Debt Financingmentioning
confidence: 99%